PENGEMBANGAN ALAT PEMBELAJARAN BERBASIS TEAM-ASSISTED INDIVIDUALIZATION (TAI) BERBASIS TEAM-ASSISTED INDIVIDUALIZATION (TAI) BERBASIS PERTANYAAN HIGHER ORDER THINKING SKILLS (HOTS) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS UNTUK SISWA KELAS 6 DALAM - Natalia Prabandari; Nunuk Suryani; Yumiati Yumiati (Widya Wacana: Jurnal Ilmiah, 2022)
This study aims to (1) develop puzzle media in learning how to read symbols/images with the Know This study aims to describe the development process, development results and produce learning tools based on Team-Assisted Individualization (TAI) with questions of Higher Order Thinking Skills (HOTS) which are effective for improving critical thinking skills for students in grade 6. This study uses research and development procedures (Research and Development). The procedure for developing TAI-based learning tools in accordance with the HOTS question approach consists of five stages, namely: analysis, design, development, implementation, and evaluation. Product trials are carried out on a small and large scale. The subjects consisted of 48 students from SD Negeri 01 Gedong, and 27 students from SD Negeri 01 Pondok. Data collection techniques using observation, questionnaires, and tests. Data analysis techniques are in the form of learning device analysis, normality analysis, and analysis of the effectiveness of TAI-based learning device products with HOTS questions. The results showed that the TAI-based learning device product with HOTS questions developed showed effectiveness in improving critical thinking skills. It can be seen from the average value of students' critical thinking skills between the pretest and posttest according to the target, namely there is a significant difference (0.000 <0.05). This means that there is a significant difference in the critical thinking ability of the sixth grade students of SD Negeri 01 Gedong and SD Negeri 01 Pondok between the pretest and posttest. There is a significant difference that shows TAI-based learning tools with HOTS questions are effective for improving critical thinking skills. Keywords: Team-Assisted Individualization, HOTS, Critical Thinking Ability